DIVERSITAS BAKTERI ENDOFIT PADA DAUN MUDA DAN TUA TUMBUHAN ANDALEH (Morus macroura miq.) - Dwi Hilda Putri; Mades Fifendy; Moca Faulina putri (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2018)
Endphytic microbes are microscopic living organisms (bacteria and fungi) that live in plant tissues (xylem and phloem), leaves, roots, fruit, and stems. These microbes live symbiosis of mutual benefit. Morus macroura miq. or Andaleh is a native plant of western Sumatra that is considered rare. The purpose of this study was to isolate and identify entophytic bacteria found in young leaves and old leaves andaleh taken from the village Andaleh, Kec. Batipuah West Sumatra. The methods used to isolate endophytic bacteria from andaleh leaves are spread plate and streak plate. Identification of endophytic bacteria in macroscopic or colony morphology. A total of 12 isolates of endophytic bacteria from young andaleh leaf and 8 isolates of endophytic bacteria from andaleh leaf. Identification Microscopic using gram staining obtained bacteria 18 gram positive endophytic bacterial isolates and 2 isolate gram negative bacteria.